Preparation and Microstructure of Ag Doped on ZnO - Anggita, Sheilla Rully; Susanto, Heri (Journal Of Natural Sciences And Mathematics Research, 2016)
Various concentration of silver (Ag) dopant on ZnO (ZnO:Ag) 2-8 mol% with solgel method were deposited on glass substrates that has been heated to a temperature of 250Â°C for 1h using a thermal spray coating technique and then annealed on 400ï°C for 1h. The obtained samples were characterized by Scanning Electron Microscopy (SEM). The effect of various Ag dopant on ZnO on the microstructure are investigated. The results showed that the microstructure ofÂ ZnO:Ag are the surface of ZnO make ganglia phase with Ag grains covered the surface. The addition concentration of Ag promotes the growth of ganglia phase and grain size. The surface of ZnO:Ag â¤4 mol% the growth grain Ag is more dominant than the growth of ZnO. The dopant Ag with a concentration of 4-8mol% ganglia structure begin to form with the presence of grains. Obtained the surface of ZnO:Ag 4 mol% begins to growth ganglia phase with the largest graindiameter is 304.8 nm. Â©2016 JNSMR UIN Walisongo. All rights reserved.